Eighteen functional monolayer metal oxides: wide bandgap semiconductors with superior oxidation resistance and ultrahigh carrier mobility. Issue 3 (20th December 2018) - Guo, Yu; Ma, Liang; Mao, Keke; Ju, Minggang; Bai, Yizhen; Zhao, Jijun; Zeng, Xiao Cheng
Abstract : 18 monolayer metals have superior oxidation resistance, wide bandgap, high carrier mobility and notable absorption in the ultraviolet region. Abstract : Layered metal oxides have emerged as an up-and-comer in the family of two-dimensional materials due to their natural abundance, intrinsic bandgap, and chemical inertness. Based on first-principles calculations, we systematically investigated the atomic structures, energetic stability, and electronic properties of 18 monolayer metal oxides. All these monolayer metal oxides are predicted to be energetically favorable with negative formation energies in the range of −4.27 to −0.47 eV per atom, suggesting good experimental feasibility for synthesis of these monolayer metal oxides. Monolayer metal oxides exhibit superior oxidation resistance, and possess modest to wide bandgaps (1.22–6.48 eV) and high carrier mobility (especially up to 8540 cm 2 V −1 s −1 for the InO monolayer), thereby rendering these low-dimensional materials promising candidates for carrier transport. Also, a pronounced in-plane anisotropy for the carrier mobility with a longitudinal/horizontal ratio as large as 115 is revealed for the monolayer metal oxides. These 2D metal oxides exhibit notable absorption in the ultraviolet range with the absorption coefficient >10 5 cm −1 . The combined novel properties of these monolayer metal oxides offer a wide range of opportunities for advanced electronic and optoelectronic applications.